ANALISIS MASLAHAH DALAM MEMBANGUN HARMONISASI PLURALISME HUKUM PADA MASYARAKAT MAJEMUK - Sugitanata, Arif; Nisa’, Ihda Shofiyatun (Al-Muqaronah: Jurnal Perbandingan Madzhab dan Hukum, 2023)
This research examines the phenomenon of legal pluralism in the context of plural societies, where ethnic, religious and cultural diversity pose challenges and opportunities in the application of diverse legal systems, including customary law, religious law and national law. Therefore, this study aims to identify and understand the interaction between these legal systems, identify the challenges that arise, and explore harmonisation strategies to support social integration and justice. The methodology used is descriptive-analytic qualitative research based on desk research to understand the dynamics of legal pluralism and use Maslahah theory as an analytical lens. The results showed that the challenges faced by pluralistic societies towards the growing legal pluralism are the birth of conflicts between norms, access to justice, and the need for legal reform. The efforts needed to achieve harmonisation of legal pluralism are by conducting dialogue between stakeholders, inclusive legal education, and adaptation to social change. The Maslahah analytical framework provides an essential perspective in evaluating harmonisation efforts, with a focus on creating social welfare and preventing harm. This research contributes to the legal literature by providing insights into how plural societies can overcome the challenges of legal pluralism and create a legal system that is fair, inclusive and responsive to the diversity of society.